IDENTIFYING THE CAUSES OF FLASH FLOODS FROM A GEOGRAPHIC PERSPECTIVE - Azmi, Nurul; Rahmadi, Rahmadi (DIVERSITY Logic Journal Multidisciplinary, 2025)
Background. A geographical approach is important to comprehensively understand the relationship between the physical conditions of an area and flash floods. One of the most devastating hydrometeorological disasters, flash floods frequently result in large losses in terms of fatalities, damage to infrastructure, and socioeconomic effects. Research Purpose. To identify the causes of flash floods from a geographic perspective. Research Method. This study employs a qualitative-descriptive literature review method to analyze and synthesize scientific sources related to the causes of flash floods from a geographical perspective. Utilizing secondary data from various journals, textbooks, official reports, and research publications, the study focuses on relevant keywords such as flash floods, topography, and geomorphology for data collection. The analysis follows three main stages: 1) data reduction of information directly linked to geographical causes, 2) thematic classification based on topography, hydrology, geomorphology, and land use, and 3) synthesis and interpretation to identify patterns and relationships among the geographical factors contributing to flash floods. Findings. Geographically speaking, steep topography, the region's geomorphological features, heavy rainfall, and changes in land use all have a significant impact on the causes of flash floods. Conclusion. Understanding and lowering the risk of flash floods through sustainable environmental management and spatial planning requires the integration of geographical analysis.